Survey of Edible Caterpillars in Gbado-Lite City (North Ubangi, Democratic Republic of the Congo) and Medicinal Value of Their Host Plants - Koto-te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina Baholy; Rakotondrazafy Jennie Irma Norosoa; Ruphin Djoza Djolu; Colette Masengo Ashande; Felix Mboka Mune; John Koyanza Wangombe-Dawe; Michel Mobale Mongeke; Jean-Jacques Domondo Amogu; Blaise Mbembo-Wa-Mbembo; Moises Monizi Mawunu (Britain International of Exact Sciences (BIoEx) Journal, 2022)
The purpose of this study was to conduct a survey of edible caterpillars and the ethno-medical value of their host plants in Gbado-Lite using the "snowball" sampling technique. The results of this study show that Anaphe panda, A. venata, Elaphrodes lactea, Imbrasia epimethea, I. oyemensis, I. truncata and Pseudanthera discrepans are the most consumed caterpillars. Drying is the most used preservation method (82.4%); ground collection is the most used harvesting method (86.3%) while evisceration (45.1%) and dehairing (33.3%) are the main cooking methods used. Harvesting is done more in the forest (94.1%) from May to July (86.3%). The vast majority (98%) of host plants are used in traditional medicine; leaves (53%) and bark (45%) are the most used parts, while decoction is the most used method of preparing therapeutic recipes (92%). The felling of trees (39%) and traditional agriculture (26%) are to varying degrees the main causes of the disappearance of edible caterpillars and their host plants. Incomplete cooking (78.4%) and/or the host plant (19.6%) are the main causes of consumer poisoning. It is therefore desirable that sustainable participatory management strategies for edible caterpillars and their host plants be put in place in North Ubangi Province. These include community agroforestry, which should be practiced in peri-urban areas in order to strengthen the resilience of communities to climate change while at the same time fighting hunger and poverty. Indeed, the domestication of species would allow annihilating the pressure on wild resources, to conserve them, to fight against deforestation and to ensure the availability and sustainability of edible caterpillars. Those phytochemical, pharmacological and toxicological studies could be carried out on host plants in order to identify compounds of medical interest contained in these plants.